Ce3+ and Tb3+ doped Ca3Gd(AlO)3(BO3)4 phosphors: synthesis, tunable photoluminescence, thermal stability, and potential application in white LEDs. Issue 18 (9th March 2018) - Li, Bin; Sun, Qi; Wang, Shaoying; Guo, Heng; Huang, Xiaoyong
Abstract : Novel thermal-stable blue-green-emitting Ca3 Gd(AlO)3 (BO3 )4 :Ce 3+, Tb 3+ phosphors were developed for near-ultraviolet-excited white LEDs. Abstract : Novel blue-green-emitting Ca3 Gd(AlO)3 (BO3 )4 :Ce 3+, Tb 3+ phosphors were successfully synthesized via traditional high temperature solid reaction method. X-ray diffraction, luminescence spectroscopy, fluorescence decay time and fluorescent thermal stability tests have been used to characterize the as-prepared samples. The energy transfer from Ce 3+ to Tb 3+ ions in the Ca3 Gd(AlO)3 (BO3 )4 host has been demonstrated to be by dipole–dipole interaction, and the energy transfer efficiency reached as high as 83.6% for Ca3 Gd0.39 (AlO)3 (BO3 )4 :0.01Ce 3+, 0.6Tb 3+ . The critical distance was calculated to be 9.44 Å according to the concentration quenching method. The emission colour of the obtained phosphors can be tuned appropriately from deep blue (0.169, 0.067) to green (0.347, 0.494) through increasing the doping concentrations of Tb 3+ . Moreover, the Ca3 Gd0.39 (AlO)3 (BO3 )4 :0.01Ce 3+, 0.6Tb 3+ phosphor possessed excellent thermal stability at high temperature, and the emission intensity at 423 K was about 87% of that at 303 K. Finally, the fabricated prototype LED device with a BaMgAl10 O7 :Eu 2+ blue phosphor, CaAlSiN3 :Eu 2+ red phosphor, Ca3 Gd0.39 (AlO)3 (BO3 )4 :0.01Ce 3+, 0.6Tb 3+ green phosphor and 365 nm-emitting InGaN chip exhibited bright warm white light. The current study shows that Ca3 Gd0.39 (AlO)3 (BO3 )4 :0.01Ce 3+, 0.6Tb 3+ can be used as a potential green phosphor for white LEDs.